“Intervenciones de enfermería en un paciente geriátrico con hemorragia digestiva alta” - Velez Buste, Gloria Estefania (2024)
Upper gastrointestinal bleeding refers to blood loss in the upper portion of the digestive tract, which includes the esophagus, stomach, and duodenum (the first part of the small intestine). This condition is characterized by the presence of blood in vomit or in the feces, as well as by the presence of digested blood in the gastric contents, known as melena. The causes can be diverse, such as peptic ulcers, gastroesophageal reflux disease, gastritis, esophagitis, esophageal varices, tumors, traumatic injuries and coagulation disorders. Symptoms range from mild abdominal discomfort or a feeling of gastric fullness to signs of hemorrhagic shock in severe cases. Diagnosis of upper gastrointestinal bleeding usually involves a detailed clinical evaluation, laboratory tests, imaging studies, and, in many cases, upper gastrointestinal endoscopy to identify the site and cause of the bleeding. The purpose of this clinical case was to carry out the clinical management of a 76-year-old geriatric patient with upper gastrointestinal bleeding and pre-existing comorbidities. Through data collection, comprehensively coordinated health interventions were carried out to address his complex clinical situation. Your entire medical history and the medications you were given during your hospital stay, and the diagnostic tests performed, are explained. In addition, a nursing assessment is carried out according to the needs of Marjorie Gordon and the NANDA, NIC and NOC methodology.